Rethinking classroom assessment with purpose in mind : - Earl, Lorna M. (Manitoba Education, Citizenship and Youth, 2006)
Rethinking Classroom Assessment with Purpose in Mind is intended to provide a framework for extending thinking, to confirm and to guide changes in effective assessment practices, and to foster professional learning. While this resource offers some common vocabulary for assessment, its focus is on ideas, rather than labels, that teachers can reflect on, discuss, and try out in classrooms. The document contains highlights from current research, descriptions of assessment processes that enhance learning, case studies from classrooms, and suggestions for professional dialogue and collaboration.